AIR FUEL RATIO CONTROL USING DELAY RESISTANT CLOSED LOOP REFERENCE MODEL ADAPTIVE CONTROL - Yildiray Yildiz (Havacılık ve Uzay Teknolojileri Dergisi, 2018)
The focus of this paper is the air fuel ratio control of spark ignited engines. It is known that for an efficient removal of the pollutants from the exhaust gases, air fuel ratio has to be kept within a narrow band around the stoicometric ratio, which represents the condition where the air amount is perfectly matched with the fuel amount for a complete burn. The main challenges for this control problem are the inherent time delay of the system and uncertain dynamics. In this paper, employment of a high performance adaptive controller, which explicitly compensates for the delays without causing excessive oscillations, is proposed. The performance of this controller is demonstrated via simulation studies. To emphasize the importance of delay compensation, the controller is compared with the closed loop model reference adaptive controller, which do not have explicit delay compensation.